Stylistic Analysis of Politeness and Pronoun Usage of the SONA of Fidel V. Ramos - Rivera, Richmond Romar (Journal of Natural Language and Linguistics, 2026)
This study aimed to examine polite expressions and pronoun usage in the SONAs of former President Fidel V. Ramos from 1992 to 1997. It employed a qualitative-descriptive research design, using the SONA of the former president as the corpus. The texts of the corpus were downloaded from the internet. To analyze the data, the researcher utilized discourse analysis to identify the polite expressions and the meanings of the personal pronouns in the SONA. The results of the study indicate that former President Fidel Ramos used polite expressions in his SONA, such as introductory remarks before he began his speech. Additionally, the phrase “Maraming Salamat po” is evident in his concluding statement. Furthermore, the study identified the usage of the pronouns: we, our, us, I, me, and my. It was revealed that the usage of “we” and “our” was particularly notable, occurring 659 and 676 times, respectively. The former president’s politeness is evident in his use of polite expressions. It can also be inferred that he is not self-centered, as he demonstrates a sense of unity with the people whenever he speaks, as shown by his usage of the pronouns “we” and “our.” By using these pronouns, he indicates that he is part of the community rather than an individual separate from the people.